PRODUCT INNOVATION STRATEGIES AMONG BANKS IN ELDORET MUNICIPALITY, KENYA - Fredrick Selfano, Odoyo; Robert, Simiyu (British Journal of Marketing Studies, 2014)
The study aimed at assessing the product innovation strategies adopted by banking industry in Eldoret, Kenya. The study was guided by the following two objectives; to assess product innovation strategies employed by banks in Eldoret, to establish the relationship between product innovation and growth of banks and to find out the challenges of product innovation strategies implementation and improvement. The study employed a survey research design of 25 banks within Eldoret municipality and targeted the branch managers and the employees in the banks who are 578. A total sample size of 191 respondents was therefore employed in the study. The study employed purposive sampling in selecting the branch managers and stratified sampling in selecting the employees. A questionnaire was used as the main data collection instrument. Descriptive and inferential statistics were both used to analyse and interpret the data. The study found out that market surveys and customers’ feedbacks had effect on product innovation strategies. The study concluded that to a large extent banks innovate new products leading to new customers (new markets). The study recommended that apart from continuous improvement of existing products, it is the responsibility of the banks to come up with new products and services to suit their target market rather than being an adopter of innovation